12 Functional outcomes following primary anterior cruciate ligament (ACL) reconstruction in south tees. (13th October 2015) - Akhtar, MA; Olatunbode, O; White, L; Hui, A
Abstract : ACL rupture is a common sports injury. ACL deficiency affect activities of daily living and participation in sports. Surgical treatment is indicated following the failure of the non-operative management. Our aim was to study the functional outcomes following ACL reconstruction. Patients undergoing ACL reconstruction between January 2009 and July 2014 were identified. Demographic details, year of surgery, number of physiotherapy session, length of treatment and functional outcomes were studied. Knee Injury and Outcome (KOOS) Score and International knee Documentation Committee (IKDC) Score was recorded at the start of rehabilitation and at the last follow up visit. Total number of patients was 383. 80 patients were female (21%) and 308 were male (79%) with a mean age of 30 y (range 14–77). The number of ACL reconstruction was 80 in 2010, 83 in 2011, 66 in 2012, 76 in 2013 and 77 in 2014. 283 patients (74%) had post op ACL rehabilitation (group A) and 100 patients (26%) were operated on after a period of prehabilitation (Group B). The mean number of physiotherapy session was 13 (range 0–65). The mean length of rehabilitation was 3 months (range 0–11 months). 163 (43%) patients successfully completed their rehabilitation and were discharged, 7 (1.8%) were listed for further surgery, 13 (3.2%) had their care transferred elsewhere and 197 (52%) did not attend to complete their rehabilitation. 55% patients in Group A and 42% in Group B did not attend to complete their rehabilitation. The mean KOOS score on referral to physiotherapy was 48 (range 3–98) and at last follow up was 82 (range 30–100) with improvement of 34 points. The mean IKDC score was 41 (range 8–35) at the start of treatment and 80 (range 34–100) at the last follow up with improvement of 39 points. There was improvement in functional scores following ACL reconstruction. We recommend prehabilitation for patients with ACL injuries to improve their compliance with the post op rehabilitation.